Microbial metabolites shape mammalian protein translation: spotlight - Tuorto, Francesca; Lyko, Frank (Cell metabolism, 2025)
Eukaryotic queuosine tRNA modification depends on the intake of microbial queuine. In a recent issue of Nature Cell Biology, Zhang et al. show that pre-queuosine 1 (preQ1), an intermediate of the bacterial queuine biosynthesis pathway, competes with queuine for the same mammalian tRNA targets to antagonistically modulate protein translation and cell proliferation.
Online verfügbar: 2. Dezember 2025, Artikelversion: 2. Dezember 2025
Gesehen am 22.01.2026